The Bride of the Nile $1 (BVolume 03s - Ebers, Georg, 1837-1898; Bell, Clara, 1834-1927 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Bride of the Nile $1 (BVolume 03" by Georg Ebers is a historical novel likely composed in the late 19th century. The story unfolds in ancient Egypt, focusing on the character of Paula, whose experiences of love, loyalty, and social conflict drive the narrative. The novel delves into themes of class, honor, and justice against the backdrop of a richly detailed historical setting. The opening of this volume finds Paula in a tumultuous emotional state after a night of intense events that leaves her restless. She observes her loyal servant Hiram embarking on a mission, which foreshadows troubles ahead as her household dynamics become increasingly strained. As conflicts arise between her affections for the innocent Hiram and the manipulative Orion, the unfolding drama teeters on the brink of interpersonal betrayal and societal repercussions, particularly in the proceedings of a court of justice. Through interactions with children, relatives, and guardians, Paula grapples with complex feelings of love, loyalty, and the quest for truth amid mounting tensions, setting the stage for a gripping exploration of character and moral dilemmas that will captivate readers. (This is an automatically generated summary.)s
Release date is 2004-04-01
This eBook was produced by David Widger
Keywords: German fiction -- Translations into English; Egypt -- History -- Fiction